Un cammino a ostacoli Neocatecumenali e Chiesa di Roma - CAMPIGLI, Francesca (Premio Istituto Sangalli per la storia religiosa, 2018)
Summer of 1968: two young Spaniards arrive in Rome with a letter and a project to export. They are Francisco (Kiko) Argüello and Carmen Hernández. So, fifty years after its foundation, the Neocatechumenal Way begins, and this volume is among the first historiographical researches about it. The overall picture arising from the comparative analysis of archival documents and unpublished texts places the Neocatechumenal Way within the historical events that affected the Church of Rome from the end of the Second Vatican Council to the present today. From the study of a minor reality, the work aims at shedding light on more general questions: from the reception of the Second Vatican Council to the relations between the episcopates; from the publication of the New Dutch Catechism to the organized entrance of laymen and laity in the Church; from the liturgical reform to 'liturgical liberalism'.